2019
DOI: 10.12890/2019_001058
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic External Jugular Vein Thrombosis

Abstract: External jugular vein thrombosis is a rare complication that, when it occurs, is usually secondary to cervical trauma, infection, venous cannulation or malignancy. By contrast, spontaneous external jugular thrombosis is extremely uncommon. We report the case of a 69-year-old woman presenting to the Emergency Department with a 3 centimetre neck lump, which had suddenly appeared on the same day. She did not have any other relevant symptoms. The patient had not suffered any recent cervical trauma or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…IJVT as thrombosis in other veins can have occlusive or non-occlusive thrombus in the lumen of the vessel. 45 The US appearance of free-floating thrombus (synonym: mobile thrombus) in the IJV is precisely described in report of Hsu et al 46 In our case, upon US examinations of the neurovascular bundles are usually visualized two artifacts: 1) edge shadowing and 2) posterior acoustic enhancement. According to Baad et al 'edge shadowing' is a refractive artifact that occurs at the edge of a significantly curved boundary (in our case boundaries of vessels) with a different speed of sound than that of the surrounding tissues.…”
Section: Ijv Anatomysupporting
confidence: 60%
See 1 more Smart Citation
“…IJVT as thrombosis in other veins can have occlusive or non-occlusive thrombus in the lumen of the vessel. 45 The US appearance of free-floating thrombus (synonym: mobile thrombus) in the IJV is precisely described in report of Hsu et al 46 In our case, upon US examinations of the neurovascular bundles are usually visualized two artifacts: 1) edge shadowing and 2) posterior acoustic enhancement. According to Baad et al 'edge shadowing' is a refractive artifact that occurs at the edge of a significantly curved boundary (in our case boundaries of vessels) with a different speed of sound than that of the surrounding tissues.…”
Section: Ijv Anatomysupporting
confidence: 60%
“…Clinical symptoms of the symptomatic IJV thrombosis should be differentiated with 1) infection of the neck, 2) lymphadenitis, 3) external jugular vein thrombosis (which occurs both unilaterally 45 and bilaterally 54 ), and 4) benign clinical conditions of the neck (infected branchial cleft cyst, etc. ), etc.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…It has been reported that idiopathic EJV thrombosis can follow in patients with cervical trauma, infection and neck malignancies. [ 5 ] In these cases, cannulation can lead to thrombus dislodgement and cannula migration leading to embolism. [ 6 ] In head-and-neck surgeries, extreme rotation of the neck (park bench, dead lateral or prone position with full neck flexion) may block EJV intraoperatively.…”
mentioning
confidence: 99%